PENGARUH KUALITAS PRODUK, HARGA, DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK VASELINE DI KABUPATEN PRINGSEWU - Nelva Ruspen; Sugiyanto Sugiyanto (CV. Adiba Aisha Amira, 2024)
Along with extreme climate change, new innovations are also urgently needed, especially in the beauty sector. Hot, dry, and humid weather creates various problems for the skin, both young and old. The changing of weather has an impact on changing people's habits with body care and changes in purchasing decisions for a product with good quality, price and image. This study aims to analyze the influence of perceptions of Product Quality, Price, and Brand Image on Vaseline beauty products in the Pringsewu Community. Data collection techniques were carried out by distributing questionnaires and the approach used was quantitative research. Data processing method using multiple linear regression method. The results of this study note that product quality has no effect on purchasing decisions, price and brand image have a positive effect on purchasing decisions.